2018
DOI: 10.24252/jb.v6i2.5378
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Synectics, Mind Maps, Cooperative Learning (Sm2cl) Terhadap Kemampuan Berpikir Kritis Siswa

Abstract: Penelitian ini bertujuan untuk menguji adanya pengaruh model pembelajaran synectics, mind maps, cooperative learning (SM2CL) terhadap kemampuan berpikir kritis siswa. Jenis penelitian quasi experiment ini memiliki sampel sebanyak 24 siswa di kelas eksperimen dan 23 siswa di kelas kontrol yang diambil secara random sampling dari populasi seluruh siswa kelas XI MIA1 MA Madani Alauddin Pao-Pao. Desain penelitian yang digunakan adalah pretest-posttes control group design. Instrumen yang digunakan berupa tes kemamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition, the ttable on df 60 was 2.000, and a significance value of 0.000 was smaller than the significance level of 5% (0.000 < 0.05). The results of this study supported previous research where the results of their research showed that the learning model Synestics, Mind Maps, Cooperative Learning (SM2CL) had a positive effect on critical thinking skills (Taufik et al, 2018). There was a difference in the results of the critical thinking ability test before and after being given treatment with the SM2CL learning model because the post-test mean score of the experimental class (87.92) was higher than the post-test average score of the control class (69.61).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the ttable on df 60 was 2.000, and a significance value of 0.000 was smaller than the significance level of 5% (0.000 < 0.05). The results of this study supported previous research where the results of their research showed that the learning model Synestics, Mind Maps, Cooperative Learning (SM2CL) had a positive effect on critical thinking skills (Taufik et al, 2018). There was a difference in the results of the critical thinking ability test before and after being given treatment with the SM2CL learning model because the post-test mean score of the experimental class (87.92) was higher than the post-test average score of the control class (69.61).…”
Section: Discussionsupporting
confidence: 90%
“…When the teacher applies mind mapping as a learning method, each student will think by interpreting, analyzing, summarizing, and evaluating/concluding the assignment and material that has been given by the teacher to further solve the material/task problem. A previous research supported this notion that the learning model Synestics, Mind Maps, Cooperative Learning (SM2CL) has a positive effect on critical thinking skills (Taufik et al, 2018).…”
Section: Introductionmentioning
confidence: 77%
“…This way, teachers can more accurately map students' critical thinking abilities. They can more easily classify which students have developed critical thinking abilities and which students have not developed and need remedial learning (Taufik et al, 2018). The infusion of the PCTS model syntax in this science teaching module is implemented in the Kurikulum Merdeka in the science curriculum for grade 7 middle school on pollution as the influence of the interaction of living things on the quality of the ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…Those with this ability will not easily stutter or be nervous when facing life's problems. Critical thinking is a skill in contemplative and argumentative thinking oriented towards what is believed so that it is done (Taufik, Mustami, & Damayanti, 2018). These capabilities include the ability to clarify the reason for decision-making, infer, elaborate, predict, and integrate various points of view, as well as additional capabilities.…”
Section: Introductionmentioning
confidence: 99%